The role of chest computed tomography (CT) as a surveillance tool in children with high‐risk neuroblastoma. Issue 6 (13th January 2015) - Federico, Sara M.; Brady, Samuel L.; Pappo, Alberto; Wu, Jianrong; Mao, Shenghua; McPherson, Valerie J.; Young, Alison; Furman, Wayne L.; Kaufman, Robert; Kaste, Sue
<x xml:space="preserve">Abstract</x> Background Standardization of imaging obtained in children with neuroblastoma is not well established. This study examines chest CT in pediatric patients with high‐risk neuroblastoma. Procedure Medical records and imaging from 88 patients with high‐risk neuroblastoma, diagnosed at St. Jude Children's Research Hospital between January, 2002 and December, 2009, were reviewed. Surveillance imaging was conducted through 2013. Ten patients with thoracic disease at diagnosis were excluded. Event free survival (EFS) and overall survival (OS) were estimated. Size specific dose estimates for CT scans of the chest, abdomen, and pelvis were used to estimate absolute organ doses to 23 organs. Organ dosimetry was used to calculate cohort effective dose. Results The 5 year OS and EFS were 51.9% ± 6.5% and 42.6% ± 6.5%, respectively. Forty‐six (58.9%) patients progressed/recurred and 41 (52.6%) died of disease. Eleven patients (14%) developed thoracic disease progression/recurrence identified by chest CT (1 paraspinal mass, 1 pulmonary nodules, and 9 nodal). MIBG (metaiodobenzylguanidine) scans identified thoracic disease in six patients. Five of the 11 had normal chest MIBG scans; three were symptomatic and two were asymptomatic with normal chest MIBG scans but avid bone disease. The estimated radiation dose savings from surveillance without CT chest imaging was 42%, 34% when accounting for modern CT acquisition (2011–2013). Conclusions Neuroblastoma progression/recurrence in the chest is rare and often presents with symptoms or is identified using standard non‐CT imaging modalities. For patients with non‐thoracic high‐risk neuroblastoma at diagnosis, omission of surveillance chest CT imaging can save 35–42% of the radiation burden without compromising disease detection. Pediatr Blood Cancer 2015;62:976–981. © 2015 Wiley Periodicals, Inc.